An improved computation method for asphalt pavement texture depth based on multiocular vision 3D reconstruction technology. (28th February 2022) - Dan, Han-Cheng; Bai, Ge-Wen; Zhu, Zhi-Heng; Liu, Xiang; Cao, Wei
Highlights: The model of pavement texture is obtained by CCD camera and 3D reconstruction. A calibration plate is developed as a portable tool to measure MTD. The slope of 3D model of pavement texture is eliminated by ICP algorithm. Create datum reference plane and texture reference plane to analyze the model. Calculate the texture depth of asphalt pavement with volume algorithm. Abstract: The depth of an asphalt pavement structure is an important index used to reflect the anti-skid performance of the pavement, which directly affects the driving safety of vehicles. In the current specifications (e.g., China, European and American standards), the mean texture depth (MTD) of an asphalt pavement is generally measured by the sand-patch method (SPM). However, SPM is easily affected by the operator's subjective experience and experimental environment, resulting in low accuracy and high scatter in the data. In view of such shortcomings, a fast and accurate method to obtain the texture depth of asphalt pavement was proposed by designing a new test tool and a computer-aided calculation method. The multiocular vision theory was adopted to reconstruct a three-dimensional (3D) point cloud model of pavement texture. To reflect the concavity and convexity of pavement texture and eliminate the influence of pavement slope, the iterative closest point (ICP) algorithm was employed to obtain the datum reference plane (DRP). On this basis, the pentahedral volume calculation method suitable for evaluating the texture depth of an asphalt pavement was proposed. Laboratory experiment results using SPM were inverted by equal volume calculation to obtain the texture reference plane (TRP) and MTD'. Meanwhile, a 3D average maximum elevation (Avg.EL) algorithm was obtained by the evolution of two-dimensional mean profile depth (MPD). Furthermore, three parameters, namely MTD, MTD', and Avg.EL, were used to measure the texture depth of two field pavement sections in service. The experimental results showed that the correlation between MTD' and MTD was better than that between Avg.EL and MTD, and the degree of scatter was smaller. MTD' could be used directly as a reference value for MTD. In the present work, the 3D volume calculation method of asphalt pavement texture depth was proposed, which integrates the technical flow of image acquisition, model reconstruction, and algorithm analysis. The developed method provides a technical reference for the application of computer vision technology in the analysis of pavement texture depth.